Analisa Performa Propeller Pada Kapal Ferry 5000 GT - Arizona Pradhika Raqih; Agus Setiawan Priyo; Nur Budiyanto Ekky (Politeknik Perkapalan Negeri Surabaya, 2018)
Nowadays, the development of propeller design planning has developed quite rapidly. Series propellers on the market are not only B-Series, Kaplan Series, AU Series, Gwan Series and SK Series. Some series propellers have characteristics of propeller design. Now there are many new series of propeller on the market which is the result of a variety of propeller series that have been there before. With technological advances, software assistance can simulate a new series of propellers with a sufficiently short period of time to get the desired propeller performance results. This research discusses the performance of B-series propellers in open water with variation of rake angle from -3 °, -2 °, -1 °, 0 °, 5 °, 10 ° and 15 ° also variation of skew angle 12 ° and 22 ° using a computational fluid dynamic method (CFD) approach. The purpose of this research is to analyze propeller model to get the highest thrust propeller model, lowest torque, highest efficiency, highest static pressure and highest velocity.